(untitled) (Research, Society and Development, 2020)
It aimed to analyze the maternal intention to breastfeed (MIB) of pregnant women and associated factors. A cross-sectional study was conducted with 94 pregnant women attending the public health service of a municipality in the South of Brazil. Information about the MIB, biological, socioeconomic, behavioral aspects related to medical history and social support were collected through semi-structured interviews. A Logistic Regression Analysis was performed to evaluate the associations. The mean gestation time was 16.92 weeks (dp:11,35), 93 pregnant women presented MIB, 89 were intended to achieve exclusive breastfeeding and 62 (70,45%) intended to do it for 6 months. There was no association between MIB exclusively for six months and the independent variables studied. Most of the women had MIB, but 15 intended to breastfeed for more than 6 months. Health professionals should act as influencers of the MIB, helping in this decision so important for the health of the mother-baby binomial.